Method for producing positive electrode active material for lithium secondary battery

The method of manufacturing a positive electrode active material by processing a lithium metal composite oxide with an element X solution and heat treatment addresses the need for improved lithium secondary battery performance, specifically enhancing initial charge and discharge efficiency and cycle characteristics.

JP2025037368APending Publication Date: 2025-03-18SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023144261
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

There is a need for improved initial charge and discharge efficiency and cycle characteristics in lithium secondary batteries as their application fields expand.

Method used

A method for manufacturing a positive electrode active material for lithium secondary batteries involves mixing a lithium metal composite oxide with water to form a slurry, followed by solid-liquid separation, passing a specific element X solution through the wet cake, and heating the resulting wet cake below 500°C.

Benefits of technology

This method enables the production of a positive electrode active material that enhances the initial charge and discharge efficiency and maintains excellent cycle characteristics in lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037368000002
    Figure 2025037368000002
  • Figure 2025037368000003
    Figure 2025037368000003
  • Figure 2025037368000004
    Figure 2025037368000004
Patent Text Reader

Abstract

To produce a positive electrode active material for a lithium secondary battery, which is capable of providing a lithium secondary battery high in initial charge / discharge efficiency and excellent in cycle characteristics.SOLUTION: A method for producing a positive electrode active material for a lithium secondary battery includes a step 1, a step 2, a step 3 and a step 4, in this order. The step 1 is a step of obtaining a slurry by mixing powder, which contains a lithium metal composite oxide that has a layered structure and contains at least Li and Ni, with a water-containing liquid. The step 2 is a step of obtaining a first wet cake, which contains the lithium metal composite oxide, and a first filtrate by subjecting the slurry obtained in the step 1 to solid-liquid separation. The step 3 is a step of obtaining a second wet cake and a second solution with an element X dissolved therein by allowing a first solution with the element X dissolved therein to pass through the first wet cake and then subjecting the wet cake after passing through the solution to solid-liquid separation. The step 4 is a step of heating the second wet cake at a temperature of 500°C or below.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery. [Background technology]

[0002] The positive electrode active material for lithium secondary batteries is an important factor that has a large effect on the battery characteristics of the lithium secondary battery. For this reason, the development of positive electrode active materials for lithium secondary batteries has been actively pursued with the aim of improving the characteristics of the lithium secondary battery.

[0003] For example, Patent Document 1 discloses a method for producing a positive electrode active material powder, which includes a step of obtaining a slurry containing powder particles coated with a precipitate by continuously adding an aqueous solution in which a lithium compound and a niobium complex are dissolved to a liquid in which powder particles of a positive electrode active material for lithium ion secondary batteries are dispersed in a mixed medium, and a step of performing solid-liquid separation of the slurry. It is said that this production method can provide a positive electrode active material powder having a lithium niobate coating layer with reduced carbon residue and low electrical resistance of the powder itself, which has a more uniform lithium niobate coating layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP-A-2014-238957 Summary of the Invention [Problem to be solved by the invention]

[0005] As the fields of application of lithium secondary batteries expand, there is a demand for further improvements in the initial charge / discharge efficiency and cycle characteristics.

[0006] An object of the present invention is to produce a positive electrode active material for a lithium secondary battery, which can provide a lithium secondary battery having high initial charge / discharge efficiency and excellent cycle characteristics.

Means for Solving the Problem

[0007] The present invention includes the following [1] to [6]. [1] A method for manufacturing a positive electrode active material for a lithium secondary battery, comprising the following steps 1, 2, 3, and 4 in this order. Step 1: A step of mixing a powder containing a lithium metal composite oxide having a layered structure and containing at least Li and Ni with a liquid containing water to obtain a slurry. Step 2: A step of performing solid-liquid separation on the slurry obtained in Step 1 to obtain a first wet cake containing the lithium metal composite oxide and a first filtrate. Step 3: A step of passing a first element X solution through the first wet cake, performing solid-liquid separation on the wet cake after passing, and obtaining a second wet cake and a second element X solution. The first element X solution is a solution in which a compound containing element X and a sulfate are dissolved, and the element X is one or more elements selected from the group consisting of Mo, V, B, Al, Nb, Ti, Y, and Si, and satisfies the following formula 1. 0 < C1(S) / C1(X) ≤ 0.5 ··· Formula 1 (In Formula 1, C1(X) is the molar concentration of the element X contained in the first element X solution, and C1(S) is the molar concentration of the sulfur element contained in the first element X solution.) Step 4: A step of heating the second wet cake at a temperature of 500 °C or lower. [2] The method for manufacturing a positive electrode active material for a lithium secondary battery according to [1], wherein Step 3 has a step of mixing a third element X solution having a higher molar concentration of the element X than the second element X solution into the second element X solution to adjust the first element X solution. [3] The method for manufacturing a positive electrode active material for a lithium secondary battery according to [1] or [2], wherein the lithium metal composite oxide is represented by the following compositional formula (I). Li[Li a (Ni (1-y-z) M1 y M2 z ) 1-a O2 (I) (In formula (I), M1 is at least one element selected from the group consisting of Co, Mn, and Al, M2 represents at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, W, Mo, Nb, Zn, V, Sn, Zr, Ga, Y, B, Si, S, and P, and -0.1 ≦ a ≦ 0.2, 0 < y ≦ 0.3, 0 ≦ z ≦ 0.1, 0 < y + z ≦ 0.3 are satisfied.) [4] The molar concentration of sulfur element contained in the first filtrate is 10 × 10 -3 mol / L or more and 100 × 10 -3 mol / L or less. A method for producing a positive electrode active material for a lithium secondary battery according to any one of [1] to [3]. [5] With respect to the lithium metal composite oxide contained in the first wet cake, the first element X solution is passed through at a weight ratio of 0.5 times or more and 4 times or less. A method for producing a positive electrode active material for a lithium secondary battery according to any one of [1] to [4]. [6] In the step 1, the mass ratio of sulfate radical contained in the powder is 1000 ppm or more and 10000 ppm or less. A method for producing a positive electrode active material for a lithium secondary battery according to any one of [1] to [5]. [Advantages of the Invention]

[0008] According to the present invention, a positive electrode active material for a lithium secondary battery can be manufactured, which can provide a lithium secondary battery having a high initial charge-discharge efficiency and excellent cycle characteristics. [Brief Description of the Drawings]

[0009] [Figure 1] It is a manufacturing process diagram of a method for manufacturing a positive electrode active material for a lithium secondary battery according to the first embodiment. [Diagram 2] It is a manufacturing process diagram of a method for manufacturing a positive electrode active material for a lithium secondary battery according to the second embodiment. [Diagram 3] It is a schematic configuration diagram showing an example of a lithium secondary battery. [Figure 4] It is a schematic diagram showing the overall configuration of an all-solid-state lithium secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, metal composite compound is hereinafter referred to as "MCC", lithium metal composite oxide is hereinafter referred to as "LiMO", and cathode active material for lithium secondary batteries is hereinafter referred to as "CAM".

[0011] "Ni" refers to nickel atoms, not nickel metal. Similarly, "Co" and "Li" refer to cobalt atoms and lithium atoms, respectively. Lithium secondary battery refers to lithium-ion secondary battery.

[0012] For example, when a numerical range is described as "1-10 μm" or "1 to 10 μm," it means a range from 1 μm to 10 μm, including the lower limit of 1 μm and the upper limit of 10 μm.

[0013] [Method for measuring initial charge / discharge efficiency] In this specification, "high initial charge / discharge efficiency" means that the initial charge / discharge efficiency measured by the method described below is 91% or more.

[0014] <Preparation of positive electrodes for lithium secondary batteries> A paste-like positive electrode mixture is prepared by adding and kneading CAM, a conductive material (acetylene black), and a binder (PVdF) in a ratio of CAM:conductive material:binder = 92:5:3 (mass ratio). When preparing the positive electrode mixture, N-methyl-2-pyrrolidone is used as an organic solvent.

[0015] The obtained positive electrode mixture is applied to a 40 μm thick Al foil as a current collector and vacuum dried at 150 °C for 8 hours to obtain a positive electrode for a lithium secondary battery. The electrode area of ​​this positive electrode for a lithium secondary battery is 1.65 cm 2 Let us assume that.

[0016] <Preparation of lithium secondary battery> The following operations are carried out in a glove box under an argon atmosphere. The above-mentioned positive electrode for lithium secondary battery is placed with the aluminum foil side facing down on the bottom cover of a part for coin-type battery R2032 (manufactured by Hosen Co., Ltd.), and a laminated film separator (thickness 16 μm) made of a heat-resistant porous layer laminated on a polyethylene porous film is placed on top of it. 300 μl of electrolyte is poured here. The electrolyte is a liquid in which LiPF6 is dissolved at a ratio of 1 mol / l in a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a ratio of 30:35:35 (volume ratio). Next, metallic lithium is used as the negative electrode, placed on the top of the separator, and the top lid is placed over the gasket and crimped with a crimping machine to produce a lithium secondary battery (coin-type half cell R2032).

[0017] The fabricated lithium secondary battery is allowed to stand at room temperature for 12 hours to allow the separator and the positive electrode mixture layer to be sufficiently impregnated with the electrolyte. At a test temperature of 25°C, the current setting value for both charging and discharging is 0.1 CA, and constant current and constant voltage charging and constant current discharging are performed, respectively. The maximum charging voltage is 4.3 V, and the minimum discharging voltage is 2.5 V. The charging capacity and discharging capacity at this time are measured, and the obtained values ​​are the initial charging capacity and initial discharging capacity, respectively.

[0018] The initial charge / discharge efficiency is calculated from the initial charge capacity and the initial discharge capacity using the following formula. Initial charge / discharge efficiency (%) = Initial discharge capacity (mAh / g) / Initial charge capacity (mAh / g) x 100

[0019] [Method of measuring cycle maintenance rate] In this specification, the term "excellent cycle characteristics" means that the capacity retention rate after 50 cycles measured by the method described below is 75% or more.

[0020] Using the lithium secondary battery after the above-mentioned measurement of the initial charge-discharge efficiency, constant current / constant voltage charge and constant current discharge are repeated under the following conditions at a test temperature of 25° C. The charge-discharge cycle is repeated 50 times. Charging: Current setting value 1CA, maximum voltage 4.3V, constant voltage constant current charging Discharge: Battery setting value 1CA, minimum voltage 2.5V, constant current discharge

[0021] The 50 cycle capacity retention rate was calculated from the discharge capacity at the 1st cycle and the discharge capacity at the 50th cycle using the following formula. A higher 50 cycle capacity retention rate indicates better cycle characteristics. Capacity retention rate at 50 cycles (%) = Discharge capacity at 50 cycles (mAh / g) / Discharge capacity at 1 cycle (mAh / g) × 100

[0022] <Method of manufacturing positive electrode active material for lithium secondary battery> The present invention is a method for producing CAM. According to the present invention, it is possible to obtain CAM in which at least a part of the surface of a LiMO particle is coated with a coating mainly composed of a lithium oxide containing element X. The coating mainly composed of a lithium oxide containing element X has lithium ion conductivity. The element X is one or more elements selected from the group consisting of Mo, V, B, Al, Nb, Ti, Y, and Si. From the viewpoint of improving the initial charge-discharge efficiency and cycle characteristics, the element X is preferably one or more elements selected from the group consisting of Mo, V, B, Nb, Ti, Y, and Si, and more preferably one or more elements selected from the group consisting of Mo, V, and Si.

[0023] Examples of the lithium oxide containing the element X include lithium molybdate, lithium vanadate, lithium borate, lithium aluminate, lithium niobate, lithium titanate, lithium yttrium oxide, and lithium silicate.

[0024] In this embodiment, "coating" means that a coating exists on part or all of the surface of the LiMO particles. The coating only needs to exist on the surface of LiMO, and it may exist on the entire surface of LiMO or on a part of the surface of LiMO.

[0025] "Taking a lithium oxide containing element X as the "main component"" means that the content of the lithium oxide containing element X among the forming materials of the coating is the highest. The content of the lithium oxide containing element X with respect to the entire coating is preferably 50 mol% or more, more preferably 60 mol% or more. Also, the content of the lithium oxide containing element X with respect to the entire coating may be 100 mol% or less.

[0026] Whether a coating containing a lithium oxide containing element X is formed on the surface of LiMO can be observed by Scanning Electron Microscope (SEM)-Energy Dispersive X-ray Spectroscopy (EDX) measurement.

[0027] The CAM obtained by the manufacturing method of this embodiment contains LiMO and a lithium oxide containing element X. The CAM contains elements, for example, in the ratio represented by formula (II). Li:Ni:M4:M3:X = (1 + x):(1 - b - c - d):b:c:d (II) (In formula (II), M4 is at least one element selected from the group consisting of Co and Mn, M3 represents at least one element selected from the group consisting of Fe, Cu, Mg, Ca, W, Zn, Sn, Zr, Ga, S, and P, X is the above element X, and formula (II) satisfies -0.1 ≤ x ≤ 0.2, 0 ≤ b ≤ 0.3, 0 ≤ c ≤ 0.1, 0.0005 ≤ d ≤ 0.1, and 0 < b + c + d ≤ 0.3.)

[0028] [Composition Analysis of CAM] The composition analysis of CAM is performed by dissolving CAM in an acid and then measuring it using an ICP emission spectroscopic analyzer. As an ICP emission spectroscopic analyzer, for example, Optima 7300 manufactured by PerkinElmer, Inc. can be used.

[0029] The method for manufacturing the above-mentioned CAM includes the following steps 1, 2, 3, and 4 in this order. Step 1: A step of mixing a powder containing LiMO having a layered structure and containing at least Li and Ni with a liquid containing water to obtain a slurry. Step 2: A step of performing solid-liquid separation on the slurry obtained in Step 1 to obtain a first wet cake containing LiMO and a first filtrate. Step 3: A step of passing a first element X solution through the first wet cake, performing solid-liquid separation on the wet cake after passing the solution, and obtaining a second wet cake and a second element X solution. The first element X solution is a solution in which a compound containing the element X and a sulfate are dissolved, and satisfies the following formula 1. 0 < C1(S) / C1(X) ≤ 0.5 ··· Formula 1 (In Formula 1, C1(X) is the molar concentration (mol / L) of the element X contained in the first element X solution, and C1(S) is the molar concentration (mol / L) of the sulfur element contained in the first element X solution.) Step 4: A step of heating the second wet cake at a temperature of 500°C or lower.

[0030] Examples of the method for manufacturing CAM include the methods of the following First Embodiment and Second Embodiment.

[0031] ≪First Embodiment≫ FIG. 1 is a process diagram showing the method for manufacturing CAM of the first embodiment. The method for manufacturing CAM shown in FIG. 1 includes steps 1, 2, 3, and 4 in this order. Hereinafter, each step will be described.

[0032] [Step 1] Step 1 is a step of mixing a powder containing LiMO with a liquid containing water to obtain a slurry. In FIG. 1, step 1 is indicated as "Step 1," the liquid containing water as "liquid," the slurry as "Slurry," and the powder containing LiMO as "LiMO."

[0033] Powder containing LiMO can be obtained by sintering a mixture of MCC and a lithium compound.

[0034] In step 1, a powder containing LiMO is put into a liquid containing water and stirred to obtain a slurry. The liquid containing water used in step 1 may be water such as pure water or ion-exchanged water, or a liquid containing water and a substance other than water. An example of the liquid containing water and a substance other than water is ammonia water. The liquid containing water preferably contains 95 mass% or more of water with respect to the total amount of the liquid.

[0035] The temperature of the aqueous liquid used is preferably room temperature (15-30°C). By controlling the temperature of the aqueous liquid within the above range, excessive elution of lithium ions from the crystal structure of LiMO into the aqueous liquid during slurry preparation can be suppressed.

[0036] The slurry in step 1 preferably contains 67 to 160 g of LiMO per 100 g of the water-containing liquid. When the content of LiMO is equal to or less than the upper limit, the excess lithium compound contained in LiMO can be removed. When the content of LiMO is equal to or more than the lower limit, the excessive elution of lithium ions from the crystal structure of LiMO into water can be suppressed.

[0037] [Process 2] Step 2 is a step of subjecting the slurry obtained in step 1 to solid-liquid separation to obtain a first wet cake containing LiMO and a first filtrate. In FIG. 1, step 2 is referred to as "Step 2", solid-liquid separation is referred to as "Solid-liquid separation", the first wet cake is referred to as "Wet cake 1", and the first filtrate is referred to as "Filtrate 1".

[0038] The solid-liquid separation means used in step 2 is not particularly limited, and a filter press, a dehydrator, a centrifugal separation type filter, a compression type filter, a pressure filter, a membrane separator, a suction filter, or the like can be used.

[0039] The molar concentration of elemental sulfur in the first filtrate, CF1(S), is 10 x 10 -3 mol / L or more, and 15×10 -3 mol / L or more is preferable, and 20×10 -3 mol / L or more. CF1(S) is preferably 100×10 -3 mol / L or less, and 90×10 -3 mol / L or less is more preferable, and 80×10 -3 mol / L or less. CF1(S) is preferably 10×10 -3 ~100×10 -3 mol / L, preferably 15×10 -3 ~90×10 -3 mol / L is more preferable, and 20×10 -3 ~80×10 -3 mol / L. When CF1(S) is in the above-mentioned range, a CAM capable of improving the initial charge / discharge efficiency and cycle characteristics can be produced. CF1(S) can be measured using an ICP emission spectrometer (Optima7300, manufactured by PerkinElmer Co., Ltd.).

[0040] [Process 3A] In step 3A, first, a first solution of element X is passed through a first wet cake. Next, the wet cake after passing the liquid is subjected to solid-liquid separation to obtain a second wet cake and a second solution containing element X. As a result, lithium oxide containing element X is arranged on the surface of the LiMO particles. In FIG. 1, step 3A is indicated as "Step 3A", the first solution of element X is indicated as "X sol. 1", the second solution of element X is indicated as "X sol. 2", and the second wet cake is indicated as "Wet cake 2".

[0041] The first element X solution in step 3A is a solution in which a compound containing element X and a sulfate are dissolved. In this specification, "dissolved" refers to the absence of solid matter when the solution is visually confirmed. The pH of the first element X solution is preferably 10 or more. When the pH of the first element X solution is 10 or more, the compound containing element X is easily dissolved. Furthermore, when LiMO comes into contact with the first element X solution, the elution of lithium ions from the crystal structure of LiMO into the element X solution can be suppressed.

[0042] The pH of the first solution of element X is defined as the value measured when the temperature of the first solution of element X is 25±5°C. When the temperature of the sampled first solution of element X is not 25±5°C, the first solution of element X is heated or cooled to 25±5°C, and then the pH is measured.

[0043] The first element X solution is prepared by mixing a solvent, a compound containing element X, and a sulfate. Examples of the solvent for the first element X solution include water, an alkaline aqueous solution, etc. When element X is Ti or Nb, ammonia water or hydrogen peroxide water may be added to the solvent.

[0044] The compound containing element X and the sulfate are added in a ratio that satisfies formula 1 above.

[0045] The compound containing element X used to prepare the first element X solution may be lithium molybdate, molybdenum oxide, vanadium oxide, lithium vanadate, aluminum oxide, aluminum hydroxide, lithium aluminate, sodium aluminate, boron oxide, boric acid, lithium borate, niobium oxide, titanium oxide, yttrium oxide, silicon dioxide, lithium silicate, or the like.

[0046] The sulfates that can be used include Li2SO4, Li2SO4·H2O, and Na2SO4.

[0047] The pH of the first solution of element X can be adjusted by adjusting the molar ratio (Li / X) of Li to element X contained in the first solution of element X. Li / X is preferably 2-4.

[0048] The first element X solution satisfies the above formula 1.

[0049] (Measuring method for C1(X) and C1(S)) C1(X) and C1(S) are obtained by measuring the first element X solution with an ICP optical emission spectrometer (Optima7300 (manufactured by PerkinElmer Co., Ltd.)).

[0050] C1(S) / C1(X) is preferably 0.015 or more, more preferably 0.02 or more, even more preferably 0.025 or more, and particularly preferably 0.03 or more. C1(S) / C1(X) is preferably 0.3 or less, more preferably 0.2 or less, and even more preferably 0.15 or less. C1(S) / C1(X) preferably satisfies any one of the following formulas 1-1 to 1-4. 0.015≦C1(S) / C1(X)≦0.3...Equation 1-1 0.02≦C1(S) / C1(X)≦0.3...Equation 1-2 0.025≦C1(S) / C1(X)≦0.2...Equation 1-3 0.03≦C1(S) / C1(X)≦0.15...Equation 1-4 When C1(S) / C1(X) is within the above range, the finally obtained CAM contains appropriate amounts of sulfur atoms and element X, and the initial charge-discharge efficiency and cycle characteristics are improved.

[0051] C1(X) is 2 x 10 -3 mol / L or more, and 5×10 -3 mol / L or more. C1(X) is 500×10 -3 mol / L or less, and 400×10 -3 mol / L or less. C1(X) is preferably 2×10 -3~500×10 -3 mol / L, preferably 5×10 -3 ~400×10 -3 When C1(X) is in the above range, the finally obtained CAM contains an appropriate amount of the element X, and the initial charge-discharge efficiency and cycle characteristics are further improved.

[0052] In step 3A, the first element X solution is passed through the first wet cake in an amount, by weight ratio, preferably 0.5 to 4 times, more preferably 1 to 3 times, and even more preferably 1.3 to 2.5 times, the amount of LiMO contained in the first wet cake.

[0053] When the amount of the first element X solution passing through the battery is within the above range, a CAM can be obtained in which a lithium oxide containing a sufficient amount of element X is present on the surface of LiMO. As a result, the initial charge-discharge efficiency and cycle characteristics of the lithium secondary battery can be further improved.

[0054] The solid-liquid separation means used in step 3A is the same as that mentioned in step 2.

[0055] [Step 4] Step 4 is a step of heating the second wet cake at a temperature of 500° C. or less. In FIG. 1, step 4 is indicated as “Step 4”. In step 4, the maximum temperature during heating is preferably less than 400° C., more preferably 100 to 350° C. The heating time is preferably 20 minutes to 12 hours. Examples of the heating device include a vacuum dryer, a rotary kiln, a roller hearth kiln, and an electric furnace.

[0056] By the step 4, crystals of the lithium oxide containing the element X grow, and the remaining moisture is removed, so that a coating containing the lithium oxide containing the element X can be formed on the surface of the LiMO. As a result, the initial charge-discharge efficiency and cycle characteristics of the lithium secondary battery can be further improved.

[0057] Second Embodiment FIG. 2 is a process chart showing a method for manufacturing a CAM according to the second embodiment. The CAM manufacturing method shown in Fig. 2 includes, in this order, step 1, step 2, step 3B, and step 4. The explanations of step 1 ("Step 1" in Fig. 2), step 2 ("Step 2" in Fig. 2), and step 4 ("Step 4" in Fig. 2) are the same as the explanations of step 1, step 2, and step 4 in the first embodiment, respectively.

[0058] When the CF1(S) contained in the first filtrate in the second embodiment is within the range described in the first embodiment, it means that the first wet cake contains an appropriate amount of sulfate radicals. When the element X solution (I) described later is passed through such a first wet cake, a second element X solution A containing sulfate radicals is obtained in step 3B described below. By using such second element X solution A, a first element X solution containing sulfate radicals can be obtained without separately adding elemental sulfur.

[0059] [Process 3B] In step 3B ("Step 3B" in FIG. 2), an element X solution (I) (not shown) is passed through the first wet cake obtained in step 2. Next, the wet cake after passing the element X solution (I) is subjected to solid-liquid separation to obtain a second wet cake A and a second element X solution A.

[0060] Next, a third solution of element X having a higher molar concentration of element X than that of the second solution of element X A is mixed with the second solution of element X A to prepare a first solution of element X. The obtained first solution of element X is passed through the first wet cake, and the wet cake after passing is subjected to solid-liquid separation to obtain a new second wet cake B and a second solution of element X B.

[0061] In FIG. 2 , step 3B is indicated as “Step 3B”, the first element X solution is indicated as “X sol.1”, the second element X solution A and the second element X solution B are indicated as “X sol.2”, and the third element X solution is indicated as “X sol.3”.

[0062] The element X solution (I) and the third element X solution used in step 3B are prepared by mixing a solvent and a compound containing element X. Examples of the compound containing element X are the same as the examples of the compound containing element X in step 3A. The solvents of the element X solution (I) and the third element X solution are the same as the examples of the solvent of the first element X solution used in step 3A. The element X solution (I) and the third element X solution are solutions in which a compound containing the element X is dissolved, and preferably have a pH (measured at 25±5° C.) of 10 or more.

[0063] The solid-liquid separation means used in step 3B is the same as that mentioned in step 2.

[0064] By passing the element X solution (I) through the first wet cake, the compound containing element X is introduced into the first wet cake, and by subjecting the wet cake after passing through to solid-liquid separation, the compound containing element X and sulfate contained in the wet cake are extracted, and a second element X solution A containing the compound containing element X and the sulfate is obtained. Examples of the sulfate include the same sulfates as those described in step 3A.

[0065] Next, the second element X solution A is mixed with the third element X solution to prepare the first element X solution. This produces a first element X solution in which the compound containing element X and sulfate are dissolved. At this time, the mixing ratio of the second element X solution A and the third element X solution is adjusted so that the first element X solution satisfies the above formula 1. The preferred range of C1(S) / C1(X) of the first element X solution is the same as the range of C1(S) / C1(X) of the first element X solution in step 3A. The explanation regarding C1(X) and pH of the first element X solution in step 3B is the same as the explanation regarding C1(X) and pH of the first element X solution in step 3A.

[0066] The third element X solution has a higher molar concentration of element X than the second element X solution A. Specifically, the molar concentration of element X in the third element X solution is preferably 1.3 to 3.0 times the molar concentration of element X in the second element X solution A. When the molar concentration of element X in the third element X solution is the above-mentioned multiple, it is easy to supply element X to the second element X solution A.

[0067] When the obtained first element X solution is passed through the first wet cake, the element X and sulfate radicals are introduced into the first wet cake. As a result, a CAM can be obtained in which a lithium oxide containing a sufficient amount of element X is present on the surface of LiMO, and the initial charge / discharge efficiency and cycle characteristics of the lithium secondary battery can be further improved.

[0068] In step 3B, the first element X solution is passed through the first wet cake in an amount, by weight ratio, preferably 0.5 to 4 times, more preferably 0.8 to 3.5 times, and even more preferably 1 to 3 times, the amount of LiMO contained in the first wet cake.

[0069] When the amount of the first element X solution passing through the battery is within the above range, a CAM can be obtained in which a lithium oxide containing a sufficient amount of element X is present on the surface of LiMO. As a result, the initial charge-discharge efficiency and cycle characteristics of the lithium secondary battery can be further improved.

[0070] By using the second element X solution A containing sulfate ions, sulfate ions can be introduced into the first wet cake without separately adding sulfate ions.

[0071] The second X element solution is mixed with the third X element solution to prepare the first X element solution, and the first X element solution is passed through the first wet cake, for example, once or more and ten times or less, or twice or more and five times or less.

[0072] (Mechanism of action) It is known that during operation of a lithium secondary battery, lithium ions diffuse between the layers inside the CAM crystal and move to the interface between the electrolyte and the particle surface. By using CAM in which lithium ions can diffuse smoothly, the initial charge / discharge efficiency and cycle characteristics are less likely to decrease, and a lithium secondary battery with a longer life can be obtained. In other words, by controlling the crystal structure of CAM to a structure in which lithium ions can diffuse more easily, and controlling the state of the CAM particle surface to a surface state in which lithium ions can diffuse more easily, the initial charge / discharge efficiency and cycle characteristics of the lithium secondary battery can be easily improved.

[0073] When the surface of LiMO particles is coated with a highly crystalline compound of a different element, the movement of lithium ions (lithium ion desorption and insertion) is restricted, and the initial charge / discharge efficiency and cycle characteristics are likely to deteriorate.

[0074] Through the study of the present inventors, it has been found that the initial charge-discharge efficiency and cycle characteristics of a battery are improved by obtaining a CAM coated with a lithium oxide containing element X using the first element X solution satisfying the above formula 1. This is presumably because when the first element X solution contains sulfate to an extent that satisfies the above formula 1, the sulfate, which is an impurity, partially inhibits the crystal growth of the lithium oxide containing element X.

[0075] It is presumed that when the crystallinity of the formed lithium oxide containing element X is low, lithium ions can diffuse in the crystal with less activation energy, improving the diffusibility of lithium ions and facilitating the improvement of the initial charge / discharge efficiency and cycle characteristics of the lithium secondary battery.

[0076] (Physical properties of LiMO) The crystal structure of LiMO is a layered structure, and is more preferably a hexagonal crystal structure or a monoclinic crystal structure.

[0077] The hexagonal crystal structure is P3, P31, P32, R3, P-3, R-3, P312, P321, P3112, P3121, P3212, P3221, R32, P3m1, P 31m, P3c1, P31c, R3m, R3c, P-31m, P-31c, P-3m1, P-3c1, R-3m, R-3c, P6, P61, P65, P62, P64, P63 , P-6, P6 / m, P63 / m, P622, P6122, P6522, P6222, P6422, P6322, P6mm, P6cc, P63cm, P63mc, P-6m2, P-6c2, P-62m, P-62c, P6 / mmm, P6 / mcc, P63 / mcm, and P63 / mmc.

[0078] In addition, the monoclinic crystal structure belongs to any one space group selected from the group consisting of P2, P21, C2, Pm, Pc, Cm, Cc, P2 / m, P21 / m, C2 / m, P2 / c, P21 / c, and C2 / c.

[0079] From the viewpoint of obtaining a lithium secondary battery having excellent initial charge / discharge efficiency and cycle characteristics, the crystal structure is more preferably a hexagonal crystal structure belonging to the space group R-3m or a monoclinic crystal structure belonging to the space group C2 / m.

[0080] [How to confirm the crystal structure] The crystal structure of LiMO can be confirmed by observation using a powder X-ray diffraction measuring device (for example, Ultima IV manufactured by Rigaku Corporation).

[0081] LiMO contains at least Li and Ni, and preferably contains Li, Ni, element M1, and element M2. Element M1 is at least one element selected from the group consisting of Co, Mn, and Al. Element M2 is at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, W, Mo, Nb, Zn, V, Sn, Zr, Ga, Y, B, Si, S, and P. LiMO is preferably represented by the following composition formula (I). Li a (Ni (1-y-z) M1y M2 z )]O2(I) (In formula (I), M1 is at least one element selected from the group consisting of Co, Mn, and Al, M2 represents at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, W, Mo, Nb, Zn, V, Sn, Zr, Ga, Y, B, Si, S, and P, and -0.1 ≦ a ≦ 0.2, 0 < y ≦ 0.3, 0 ≦ z ≦ 0.1, 0 < y + z ≦ 0.3 are satisfied.)

[0082] From the viewpoint of obtaining a lithium secondary battery with excellent cycle characteristics, a in the composition formula (I) is preferably -0.05 or more, more preferably more than 0, and even more preferably 0.02 or more. Also, from the viewpoint of obtaining a lithium secondary battery with a higher initial coulombic efficiency, a in the formula (I) is preferably 0.1 or less, and more preferably 0.08 or less.

[0083] The upper and lower limit values of a can be arbitrarily combined. a is preferably -0.1 to 0.2, more preferably -0.05 to 0.1, and even more preferably more than 0 and 0.08 or less.

[0084] From the viewpoint of obtaining a lithium secondary battery with excellent cycle characteristics, y in the composition formula (I) is preferably 0.01 or more, and more preferably 0.02 or more. Also, y in the composition formula (I) is preferably 0.25 or less, and more preferably 0.2 or less.

[0085] The upper and lower limit values of y can be arbitrarily combined. y is preferably 0.01 to 0.25, and more preferably 0.02 to 0.2.

[0086] When LiMO contains M2, from the viewpoint of obtaining a lithium secondary battery with low internal resistance, z in the composition formula (I) is preferably 0.005 or more, more preferably 0.01 or more, and even more preferably 0.05 or more. z in the formula (I) is preferably 0.08 or less, and more preferably 0.05 or less.

[0087] The upper limit and lower limit of z can be combined in any combination. z is preferably 0 to 0.08, more preferably 0.005 to 0.08, further preferably 0.01 to 0.08, and particularly preferably 0.05 to 0.05.

[0088] The value of y+z in the composition formula (I) is preferably 0.25 or less, and more preferably 0.2 or less, from the viewpoint of obtaining a lithium secondary battery having a high initial capacity and excellent cycle characteristics. From the viewpoint of suppressing an increase in the resistance of the battery after repeated charge-discharge cycles, the value of y+z is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.05 or more.

[0089] The upper limit and lower limit of the value of y+z can be combined in any desired manner. y+z is preferably from 0.01 to 0.3, more preferably from 0.02 to 0.25, and even more preferably from 0.05 to 0.2.

[0090] From the viewpoint of obtaining a lithium secondary battery having excellent cycle characteristics, M2 is more preferably one or more elements selected from the group consisting of Ti, Mg, W, Nb, and Zr, and M1 may be at least two or more elements selected from the group consisting of Co, Mn, and Al.

[0091] [Composition analysis of LiMO] The composition of LiMO is analyzed by dissolving LiMO powder in hydrochloric acid and then measuring it using an ICP optical emission spectrometer. As an ICP emission spectrometer, for example, Optima 7300 manufactured by PerkinElmer Co., Ltd. can be used.

[0092] The powder containing LiMO contains sulfate radicals (SO4 2- ). Here, examples of raw materials from which sulfate radicals are derived include metal sulfates such as nickel sulfate, manganese sulfate, aluminum sulfate, and cobalt sulfate. The mass ratio of sulfate radicals contained in the powder is preferably 1000 ppm or more, more preferably 1500 ppm or more, and even more preferably 2000 ppm or more. The mass ratio of sulfate radicals contained in the powder is preferably 10000 ppm or less, more preferably 9000 ppm or less, and even more preferably 8000 ppm or less. The mass ratio of sulfate radicals contained in the powder is preferably 1000-10000 ppm, more preferably 1500-9000 ppm or more, and even more preferably 2000-8000 ppm or more. When the mass ratio of the sulfate radical contained in the powder is within the above-mentioned range, the first filtrate in steps 3A and 3B and the first element X solution in step 3B contain an appropriate amount of sulfur atoms, which contributes to improving the initial charge / discharge efficiency and cycle characteristics of the lithium secondary battery.

[0093] (Method for measuring mass ratio of sulfate radical) The mass ratio of sulfate radicals contained in the powder was measured by dissolving the powder containing LiMO and then using an ICP emission spectrometer (Optima 7300 (PerkinElmer Co., Ltd.)). The obtained sulfur atom content was calculated as sulfate radicals (SO - ) is the converted value.

[0094] (Production of powder containing LiMO) The powder containing LiMO preferably includes a step of obtaining MCC and a step of obtaining LiMO. Hereinafter, the step of obtaining MCC and the step of obtaining LiMO will be described in that order.

[0095] [Process for obtaining MCC] The MCC may be a metal composite hydroxide, a metal composite oxide, or a mixture thereof, containing at least Ni. The MCC preferably contains Ni and the element M1, and may also contain the element M2. It can be produced by a batch coprecipitation method or a continuous coprecipitation method. Hereinafter, the production method will be described in detail using a metal composite oxide containing Ni and element M1 as an example.

[0096] First, a nickel salt solution, a metal salt solution containing element M1, and a complexing agent are reacted by the continuous coprecipitation method described in JP-A-2002-201028 to obtain Ni (1-y) M1 y A metal composite hydroxide represented by (OH)2 (wherein y is the same as y in the above composition formula (I)) is produced.

[0097] The nickel salt that is the solute of the nickel salt solution is not particularly limited, but for example, any one or more of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate can be used.

[0098] Examples of metal salts that are solutes of the metal salt solution containing element M1 include sulfates, chlorides, acetates, hydroxides, etc. of element M1. For example, cobalt sulfate, cobalt nitrate, cobalt chloride, manganese sulfate, manganese nitrate, manganese chloride, manganese acetate, aluminum sulfate, sodium aluminate, etc. can be used.

[0099] The above metal salts are (1-y) M1 y It is used in a ratio corresponding to the composition ratio of (OH)2. Water is also used as the solvent.

[0100] The complexing agent is a compound capable of forming a complex with Ni and ions of element M1 in an aqueous solution, for example, ammonium ion donors, hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine.

[0101] Examples of the ammonium ion donor include ammonium salts such as ammonium hydroxide, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride.

[0102] A complexing agent may not be included, and when a complexing agent is included, the amount of the complexing agent included in the mixed liquid containing the nickel salt solution, the metal salt solution containing element M1, and the complexing agent is, for example, a molar ratio of the amount of the complexing agent to the total number of moles of the metal salts that is greater than 0 and less than or equal to 2.0.

[0103] In the coprecipitation method, in order to adjust the pH value of the mixed solution containing the nickel salt solution, the metal salt solution containing element M1, and the complexing agent, an alkaline aqueous solution is added to the mixed solution before the pH of the mixed solution changes from alkaline to neutral. The alkaline aqueous solution can be a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution.

[0104] The pH value of the mixed liquid is defined as the value measured when the temperature of the mixed liquid is 40° C. The pH of the mixed liquid is measured when the temperature of the mixed liquid sampled from the reaction tank reaches 40° C.

[0105] During the reaction, the temperature of the reaction vessel is controlled within the range of, for example, 20 to 80°C, preferably 30 to 70°C.

[0106] During the reaction, the pH value in the reaction tank is controlled within the range of, for example, 9 to 13, and preferably 11 to 13.

[0107] The materials in the reaction vessel are mixed by suitable stirring. The reaction vessel used in the continuous coprecipitation method may be a reaction vessel in which the formed reaction precipitate is allowed to overflow for separation.

[0108] In order to control the inside of the reaction vessel to a desired atmosphere, a specific gas may be passed through the reaction vessel or the reaction liquid may be directly bubbled into the reaction vessel. After the above reaction, the resulting reaction precipitate is washed with water and dried to obtain a metal composite hydroxide. In addition, if impurities derived from the mixed liquid remain on the reaction precipitate simply by washing with water, the reaction precipitate may be washed with weak acid water or an alkaline solution containing sodium hydroxide or potassium hydroxide, as necessary.

[0109] After drying the reaction precipitate, it may be classified as appropriate.

[0110] When a metal composite oxide is used as the MCC, the metal composite oxide can be obtained by heating the metal composite hydroxide, for example, at 300-700° C. for 0.1-10 hours in an oxygen or air atmosphere.

[0111] [Step for obtaining powder containing LiMO] The process for obtaining a powder containing LiMO includes a mixing process of mixing MCC with a lithium compound, and a firing process of firing the resulting mixture.

[0112] ·Mixing process The MCC and the lithium compound are mixed. The lithium compound may be at least one of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium hydroxide hydrate, lithium oxide, lithium chloride, and lithium fluoride. Among these, at least one of lithium hydroxide, lithium hydroxide hydrate, and lithium carbonate is preferred.

[0113] The lithium compound and MCC are mixed in consideration of the composition ratio of the final target product to obtain a mixture of the lithium compound and MCC. The amount (molar ratio) of Li relative to the total amount of metal elements contained in MCC is preferably 0.9 to 1.10, more preferably 0.91 to 1.10, and even more preferably 0.92 to 1.10.

[0114] · Firing process The resulting mixture is fired. By firing the mixture, LiMO crystals grow. For firing, dry air, an oxygen atmosphere, an inert atmosphere, or the like is used depending on the desired composition. In this embodiment, firing in an oxygen atmosphere is preferred. At this time, the oxygen concentration is preferably higher than that of the air.

[0115] The firing process may involve only one firing step, or may involve multiple firing steps. In the case of multiple firing steps, the step in which the firing is performed at the highest temperature is referred to as the main firing. Prior to the main firing, a preliminary firing may be performed at a temperature lower than that of the main firing. In addition, after the main firing, a post-firing may be performed at a temperature lower than that of the main firing.

[0116] In this embodiment, it is preferable to first calcinate the mixture and then calcinate it.

[0117] The calcination temperature of the pre-calcination is preferably 600 to 900° C., more preferably 610 to 850° C., and even more preferably 620° C. or more and less than 700° C. When the calcination temperature is equal to or more than the lower limit of the above range, a powder containing LiMO having a strong crystal structure can be obtained. When the calcination temperature is equal to or less than the upper limit of the above range, the volatilization of lithium ions on the surface of LiMO particles can be reduced.

[0118] The firing temperature in the main firing is preferably 600 to 900° C., more preferably 650 to 850° C., and even more preferably 700 to 820° C. When the firing temperature is equal to or higher than the lower limit of the above range, a powder containing LiMO having a strong crystal structure can be obtained. When the firing temperature is equal to or lower than the upper limit of the above range, the volatilization of lithium ions on the surface of LiMO particles can be reduced.

[0119] The retention time for each of the pre-baking and main baking is preferably 1 to 50 hours, more preferably 2 to 20 hours. When the retention time for baking is equal to or less than the upper limit of the above range, the volatilization of lithium ions is suppressed, and the deterioration of the initial charge / discharge efficiency and cycle characteristics is suppressed. When the retention time for baking is equal to or more than the lower limit of the above range, the development of crystals is promoted, and the deterioration of the battery performance is suppressed.

[0120] The firing temperature in this specification refers to the temperature of the atmosphere in the firing furnace, and means the maximum holding temperature.

[0121] After the calcination or main calcination, the mixture may be crushed appropriately. By the above steps, a powder containing LiMO is obtained.

[0122] <Lithium secondary battery> A positive electrode for a lithium secondary battery suitable for use with the CAM produced by the present embodiment will be described below. Hereinafter, the positive electrode for a lithium secondary battery may be referred to as a positive electrode. Furthermore, a lithium secondary battery suitable for use as a positive electrode will be described.

[0123] An example of a suitable lithium secondary battery when using the CAM produced by this embodiment has a positive electrode, a negative electrode, a separator sandwiched between the positive electrode and the negative electrode, and an electrolyte solution disposed between the positive electrode and the negative electrode.

[0124] 3 is a schematic diagram showing an example of a lithium secondary battery. For example, a cylindrical lithium secondary battery 10 is manufactured as follows.

[0125] First, as shown in the partially enlarged view of FIG. 3 , a pair of strip-shaped separators 1, a strip-shaped positive electrode 2 having a positive electrode lead 21 at one end, and a strip-shaped negative electrode 3 having a negative electrode lead 31 at one end are laminated in the order of separator 1, positive electrode 2, separator 1, and negative electrode 3, and then wound to form an electrode group 4.

[0126] The positive electrode 2, for example, has a positive electrode active material layer 2a containing CAM, and a positive electrode current collector 2b on one surface of which the positive electrode active material layer 2a is formed. Such a positive electrode 2 can be manufactured by first preparing a positive electrode mixture containing CAM, a conductive material, and a binder, and supporting the positive electrode mixture on one surface of the positive electrode current collector 2b to form the positive electrode active material layer 2a.

[0127] Examples of the negative electrode 3 include an electrode in which a negative electrode mixture containing a negative electrode active material (not shown) is supported on a negative electrode current collector, and an electrode made of only the negative electrode active material. The negative electrode 3 can be manufactured in a manner similar to that for the positive electrode 2.

[0128] Next, the electrode group 4 and an insulator (not shown) are housed in the battery can 5, the bottom of the can is sealed, the electrode group 4 is impregnated with an electrolyte solution 6, and the electrolyte is disposed between the positive electrode 2 and the negative electrode 3. Furthermore, the upper part of the battery can 5 is sealed with a top insulator 7 and a sealing body 8, whereby a lithium secondary battery 10 can be manufactured.

[0129] The shape of the electrode group 4 can be, for example, a columnar shape such that the cross-sectional shape when the electrode group 4 is cut perpendicular to the winding axis is a circle, an ellipse, a rectangle, or a rectangle with rounded corners.

[0130] The shape of a lithium secondary battery having such an electrode group 4 can be any shape defined by IEC60086, which is a standard for batteries defined by the International Electrotechnical Commission (IEC), or JIS C 8500. For example, cylindrical or rectangular shapes can be used.

[0131] Furthermore, the lithium secondary battery is not limited to the above-mentioned wound type configuration, and may be a laminated type configuration in which a laminated structure of a positive electrode, a separator, a negative electrode, and a separator is repeatedly stacked. Examples of the laminated type lithium secondary battery include a so-called coin type battery, a button type battery, and a paper type (or sheet type) battery.

[0132] For the positive electrode, separator, negative electrode, and electrolyte constituting the lithium secondary battery, for example, the configurations, materials, and manufacturing methods described in

[0113] to

[0140] of WO2022 / 113904A1 can be used.

[0133] <All-solid-state lithium secondary battery> The CAM produced according to this embodiment can be used as a CAM for an all-solid-state lithium secondary battery.

[0134] Fig. 4 is a schematic diagram showing an example of an all-solid-state lithium secondary battery. The all-solid-state lithium secondary battery 1000 shown in Fig. 4 has a laminate 100 having a positive electrode 110, a negative electrode 120, and a solid electrolyte layer 130, and an exterior body 200 that houses the laminate 100. The all-solid-state lithium secondary battery 1000 may also have a bipolar structure in which a CAM and a negative electrode active material are arranged on both sides of a current collector. A specific example of the bipolar structure is the structure described in JP-A-2004-95400.

[0135] The positive electrode 110 has a positive electrode active material layer 111 and a positive electrode current collector 112. The positive electrode active material layer 111 contains the above-mentioned CAM and a solid electrolyte. The positive electrode active material layer 111 may also contain a conductive material and a binder.

[0136] The negative electrode 120 has a negative electrode active material layer 121 and a negative electrode current collector 122. The negative electrode active material layer 121 contains a negative electrode active material. The negative electrode active material layer 121 may also contain a solid electrolyte and a conductive material.

[0137] The laminate 100 may have an external terminal 113 connected to the positive electrode current collector 112 and an external terminal 123 connected to the negative electrode current collector 122. In addition, the all-solid-state lithium secondary battery 1000 may have a separator between the positive electrode 110 and the negative electrode 120.

[0138] The all-solid-state lithium secondary battery 1000 further includes an insulator (not shown) that insulates the laminate 100 from the exterior body 200 , and a sealing body (not shown) that seals the opening 200 a of the exterior body 200 .

[0139] A container molded from a highly corrosion-resistant metal material such as aluminum, stainless steel, or nickel-plated steel can be used as the exterior body 200. Also, a container formed into a bag shape from a laminate film having at least one surface treated to be corrosion-resistant can be used as the exterior body 200.

[0140] Examples of the shape of the all-solid-state lithium secondary battery 1000 include a coin type, a button type, a paper type (or a sheet type), a cylindrical type, a square type, and a laminate type (pouch type).

[0141] The all-solid-state lithium secondary battery 1000 is illustrated as having one laminate 100 as an example, but the present embodiment is not limited to this. The all-solid-state lithium secondary battery 1000 may have a configuration in which the laminate 100 is used as a unit cell, and a plurality of unit cells (laminated bodies 100) are sealed inside an exterior body 200.

[0142] For the all-solid-state lithium secondary battery, for example, the configuration, materials, and manufacturing method described in

[0151] to

[0181] of WO2022 / 113904A1 can be used.

[0143] Furthermore, the positive electrode having the above-mentioned configuration has excellent initial charge-discharge efficiency and cycle characteristics because it has the CAM having the above-mentioned configuration.

[0144] Furthermore, since the lithium secondary battery having the above-mentioned configuration has the above-mentioned positive electrode, it becomes a secondary battery excellent in initial charge / discharge efficiency and cycle characteristics.

[0145] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention.

[0146] The present invention further includes the following aspects

[21] to

[26] .

[21] A method for producing a CAM, comprising the steps 1, 2, 3, and 4 described below in this order. Step 3: A step of passing a first solution containing element X through the first wet cake, and subjecting the wet cake after passing through to solid-liquid separation to obtain a second wet cake and a second solution containing element X. The first element X dissolution solution is a dissolution solution in which a compound containing the element X and a sulfate are dissolved, and satisfies the above formula 1-2.

[22] The step 3 has a step of mixing a third element X dissolution solution having a molar concentration of the element X higher than that of the second element X dissolution solution into the second element X dissolution solution to adjust the first element X dissolution solution, according to the manufacturing method of the CAM described in

[21] .

[23] The LiMO is represented by the above compositional formula (I), according to the manufacturing method of the CAM described in

[21] or

[22] .

[24] The CF1(S) of the first filtrate is 20×10 -3 ~80×10 -3 mol / L, according to the manufacturing method of the CAM described in any one of

[21] to

[23] .

[25] The first element X dissolution solution is passed through the LiMO contained in the first wet cake at a weight ratio of 1 to 3 times, according to the manufacturing method of the CAM described in any one of

[21] to

[24] .

[26] In the step 1, the mass ratio of the sulfate radical contained in the LiMO is 2000-8000 ppm, according to the manufacturing method of the CAM described in any one of

[21] to

[25] .

[27] In the step 3, the first element X dissolution solution satisfies the above formula 1-3, according to the manufacturing method of the CAM described in any one of

[21] to

[26] .

Example

[0147] Next, the present invention will be described in more detail by way of examples.

[0148] <Measurement of the mass ratio of sulfate radical> The mass ratio of the sulfate radical contained in the powder containing LiMO was measured by the method described in the above (Measurement method of the mass ratio of sulfate radical).

[0149] <Measurement method of C1(X) and C1(S)> C1(X) and C1(S) were measured by the method described in the above (Measurement method of C1(X) and C1(S)), and C1(S) / C1(X) was calculated.

[0150] The compositional analyses of CAM and LiMO were carried out by the methods described above in [Compositional Analysis of CAM] and [Compositional Analysis of LiMO], respectively. The molar concentration of element X in each of the element X solutions and the CF1(S) of the first filtrate were measured using an ICP emission spectrometer (Optima 7300, manufactured by PerkinElmer Co., Ltd.).

[0151] <Method for measuring initial charge / discharge efficiency> The initial charge / discharge efficiency of the lithium secondary battery was measured by the method explained in [Method of measuring initial charge / discharge efficiency] above. <Method of measuring cycle maintenance rate> The cycle retention rate of the lithium secondary battery was measured by the method explained in the above [Method of measuring cycle retention rate].

[0152] <Comparative Example 1> A nickel-cobalt-manganese composite hydroxide, MCC1, was obtained by the continuous coprecipitation method described in JP-A-2002-201028. The molar ratio of MCC1 was Ni:Co:Mn=83:12:5 in elemental analysis by ICP emission spectrometry. MCC1 and lithium hydroxide monohydrate were mixed at a ratio such that the molar ratio Li / (Ni+Co+Mn) of the amount of Li to the total amount 1 of Ni, Co, and Mn contained in MCC1 was 1.08, to obtain mixture 1. The obtained mixture 1 was pre-fired at 650°C for 5 hours in an atmosphere containing oxygen gas, and the pre-fired product was crushed. Next, the crushed pre-fired product was fired at 800°C for 5 hours in an oxygen atmosphere and crushed to obtain a powder containing LiMO-1. In the composition formula (I), LiMO-1 has a=0.08, y=0.17, z=0, M1=Co and Mn, and the powder contained 7000 ppm of sulfate radicals. As a result of powder X-ray diffraction measurement, LiMO-1 had a layered structure.

[0153] Water, lithium hydroxide monohydrate, and lithium molybdate (Li2MoO4) were stirred to dissolve the lithium molybdate, and a molybdenum solution (I) was obtained. The molar concentration of Mo in the molybdenum solution (I) was 140×10 -3It was confirmed that the Li / Mo (molar ratio) was 2.1 and the pH was greater than 10.

[0154] A powder containing LiMO-1 per 100 g was mixed with 100 g of pure water at room temperature to obtain a slurry. The slurry was stirred for 20 minutes and then filtered (solid-liquid separation) using a suction filter to obtain a first filtrate C1 and a first wet cake 1. The CF1(S) of the first filtrate C1 was 62×10 -3 The concentration was mol / L. Next, the first wet cake 1 was placed on a filter paper of a suction filtration device, and a molybdenum solution (I) was passed through the first wet cake 1 while suctioning, and the solution was filtered to obtain a second wet cake 1 and a second molybdenum solution C1. The second wet cake C1 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-C1. As a result of composition analysis, CAM-C1 contained Li, Ni, Co, Mn, Mo, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.0003, and d = 0.001.

[0155] <Example 1> Water, lithium hydroxide monohydrate, and lithium molybdate were stirred to dissolve the lithium molybdate, and a second molybdenum solution C1 having a molar concentration of 200×10 -3 80 g of the second molybdenum solution C1 obtained in Comparative Example 1 and 20 g of the third molybdenum solution 1-1 were mixed to prepare a third molybdenum solution 1-1 having a molar concentration of Mo of 140×10 -3 The first wet cake 1 obtained in Comparative Example 1 was placed on filter paper of a suction filtration device, and the first molybdenum solution 1-1, which was twice the amount of LiMO-1 by weight, was passed through the first wet cake 1 while performing suction, and further filtration (solid-liquid separation) was performed to obtain a second wet cake 1-1 and a second molybdenum solution 1-1.

[0156] 80 g of the second molybdenum solution 1-1 and 20 g of the third molybdenum solution 1-1 were mixed to obtain a first molybdenum solution 1-2. The C1(S) of the first molybdenum solution 1-2 was 4.4×10 -3 mol / L, C1(X) is 140×10 -3 mol / L, and C1(S) / C1(X)=0.031. The first wet cake 1 obtained in Comparative Example 1 was placed on a suction filter, and a first molybdenum solution 1-2, which was twice the weight ratio of LiMO-1, was passed through the first wet cake 1, and further filtered to obtain a second wet cake 1-2 and a second molybdenum solution 1-2. The second wet cake 1-2 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-1. As a result of composition analysis, CAM-1 contained Li, Ni, Co, Mn, Mo, and S, and in the formula (II), x=0.01, b=0.17, c=0.0003, and d=0.001.

[0157] <Example 2> Water, lithium hydroxide monohydrate, lithium molybdate, and lithium sulfate monohydrate (Li2SO4·H2O) were stirred and dissolved to prepare a first molybdenum solution 2. The C1(S) of the first molybdenum solution 2 was 7.2×10 -3 mol / L, C1(X) is 140×10 -3 mol / L, and C1(S) / C1(X) = 0.051.

[0158] The first wet cake 1 obtained in Comparative Example 1 was placed on a filter paper of a suction filtration device, and a first molybdenum solution 2, which was twice the weight ratio of LiMO-1, was passed through the first wet cake 1 while performing a suction operation, and further filtration was performed to obtain a second wet cake 2 and a second molybdenum solution 2. The second wet cake 2 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer, and CAM-2 was obtained. As a result of composition analysis, CAM-2 contained Li, Ni, Co, Mn, Mo, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.0006, and d = 0.002.

[0159] <Example 3> Water, lithium hydroxide monohydrate, vanadium oxide, and lithium sulfate monohydrate (Li2SO4·H2O) were stirred and dissolved to prepare a first vanadium solution 3. The C1(S) of the first vanadium solution 3 was 16×10 -3 mol / L, C1(X) is 88×10 -3 mol / L, and C1(S) / C1(X) = 0.18.

[0160] The first wet cake 1 obtained in Comparative Example 1 was placed on a filter paper of a suction filtration device, and while performing a suction operation, a first vanadium solution 3 was passed through the first wet cake 1 in a weight ratio twice that of LiMO-1, and further filtered to obtain a second wet cake 3 and a second vanadium solution 3. The second wet cake 3 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-3. As a result of composition analysis, CAM-3 contained Li, Ni, Co, Mn, V, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.0006, and d = 0.003.

[0161] <Example 4> Water, lithium hydroxide monohydrate, 20 wt% lithium polysilicate (Li2Si5O 11 The first silicon solution 4 was prepared by stirring and dissolving the silicon solution 4 and lithium sulfate monohydrate (Li2SO4·H2O). The C1(S) of the first silicon solution 4 was 7.8×10 -3 mol / L, C1(X) is 91×10 -3 mol / L, and C1(S) / C1(X) = 0.086.

[0162] The first wet cake 1 obtained in Comparative Example 1 was placed on a filter paper of a suction filtration device, and while performing a suction operation, a first silicon dissolution 4, which is twice the weight ratio of LiMO-1, was passed through the first wet cake 1, and further filtration was performed to obtain a second wet cake 4 and a second silicon dissolution 4. The second wet cake 4 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-4. As a result of composition analysis, CAM-4 contained Li, Ni, Co, Mn, Si, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.0006, and d = 0.006.

[0163] <Comparative Example 2> Water, lithium hydroxide monohydrate, 20 wt% lithium polysilicate (Li2Si5O 11 The first silicon dissolution solution C2 was prepared by stirring and dissolving the solution of silicon dioxide (SiO2) and lithium sulfate monohydrate (Li2SO4·H2O). The C1(S) of the first silicon dissolution solution C2 was 195×10 -3 mol / L, C1(X) is 91×10 -3 mol / L, and C1(S) / C1(X) = 2.2.

[0164] The first wet cake 1 obtained in Comparative Example 1 was placed on a filter paper of a suction filtration device, and while performing a suction operation, a first silicon dissolution C2, which is twice the weight ratio of LiMO-1, was passed through the first wet cake 1, and further filtration was performed to obtain a second wet cake C2 and a second silicon dissolution C2. The second wet cake C2 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-C2. As a result of composition analysis, CAM-C2 contained Li, Ni, Co, Mn, Si, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.01, and d = 0.007.

[0165] <Comparative Example 3> Water, lithium hydroxide monohydrate, and lithium sulfate monohydrate (LiSO·HO) were stirred to dissolve the sulfur element at a molar concentration of 7.8×10 -3 A first lithium sulfate solution C3 having a concentration of 1.0 mol / L was prepared. The first wet cake 1 obtained in Comparative Example 1 was placed on a filter paper of a suction filtration device, and a first lithium sulfate solution C3, which was twice the weight ratio of LiMO-1, was passed through the first wet cake 1 while performing a suction operation, and further filtration was performed to obtain a second wet cake C3 and a second lithium sulfate solution C3. The second wet cake C3 was heated at a maximum temperature of 190°C for 3 hours using a vacuum dryer to obtain CAM-C3. As a result of composition analysis, CAM-C3 contained Li, Ni, Co, Mn, and S, and in the formula (II), x = 0.01, b = 0.17, c = 0.0006, and d = 0.

[0166] [Table 1]

[0167] As shown in Table 1, it was confirmed that the lithium secondary battery using LiMO produced by the manufacturing method of the embodiment as the CAM had a higher initial charge / discharge efficiency and superior cycle characteristics than the lithium secondary battery using LiMO produced by the manufacturing method of the comparative example as the CAM. [Explanation of symbols]

[0168] 1: separator, 2: positive electrode, 2a: positive electrode active material layer, 2b: positive electrode current collector layer, 3: negative electrode, 4: electrode group, 5: battery can, 6: electrolyte, 7: top insulator, 8: sealing body, 10: lithium secondary battery, 21: positive electrode lead, 31: negative electrode lead, 100: laminate, 110: positive electrode, 111: positive electrode active material layer, 112: positive electrode current collector, 113: external terminal, 120: negative electrode, 121: negative electrode active material layer, 122: negative electrode current collector, 123: external terminal, 130: solid electrolyte layer, 200: exterior body, 200a: opening, 1000: all-solid-state lithium secondary battery

Claims

1. A method for producing a positive electrode active material for a lithium secondary battery, comprising the following steps 1, 2, 3, and 4 in this order: Step 1: A step of mixing a powder containing a lithium metal composite oxide having a layered structure and containing at least Li and Ni with a liquid containing water to obtain a slurry. Step 2: A step of subjecting the slurry obtained in the step 1 to solid-liquid separation to obtain a first wet cake containing the lithium metal composite oxide and a first filtrate. Step 3: A step of passing a first solution containing element X through the first wet cake, and subjecting the wet cake after passing through to solid-liquid separation to obtain a second wet cake and a second solution containing element X. The first element X solution is a solution in which a compound containing the element X and a sulfate are dissolved, and the element X is one or more elements selected from the group consisting of Mo, V, B, Al, Nb, Ti, Y, and Si, and satisfies the following formula 1. 0<C1(S) / C1(X)≦0.5...Formula 1 (In formula 1, C1(X) is the molar concentration of the element X contained in the first element X solution, and C1(S) is the molar concentration of the sulfur element contained in the first element X solution.) Step 4: heating the second wet cake at a temperature less than or equal to 500°C.

2. 2. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the step 3 comprises a step of mixing a third element X solution having a molar concentration of the element X higher than that of the second element X solution with the second element X solution to prepare a first element X solution.

3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1 or 2, wherein the lithium metal composite oxide is represented by the following composition formula (I): L[L) a (N (1-y-z) M1 y M2 z ) 1-a ]O 2 (I) (In formula (I), M1 represents at least one element selected from the group consisting of Co, Mn, and Al, and M2 represents at least one element selected from the group consisting of Fe, Cu, Ti, Mg, Ca, W, Mo, Nb, Zn, V, Sn, Zr, Ga, Y, B, Si, S, and P, and satisfies −0.1≦a≦0.2, 0<y≦0.3, 0≦z≦0.1, and 0<y+z≦0.3.)

4. The molar concentration of elemental sulfur contained in the first filtrate is 10×10 -3 mol / L or more 100×10 -3 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the concentration of the positive electrode active material is 1.0 mol / L or less.

5. 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein the first element X solution is passed through the first wet cake in an amount of 0.5 to 4 times by weight relative to the lithium metal composite oxide contained in the first wet cake.

6. 3. The method for producing a positive electrode active material for a lithium secondary battery according to claim 1, wherein in the step 1, a mass ratio of sulfate radicals contained in the powder is 1000 ppm or more and 10000 ppm or less.

Citation Information

Patent Citations

  • Positive electrode active material powder, and manufacturing method thereof

    JP2014238957A